Breaking Barriers: Examining Inclusive Education in Islamic Schools through the Merdeka Belajar Curriculum - Khofidotur Rofiah; Farida Isroani; Muhammad Nurrohman Jauhari (Universitas PGRI Adi Buana Surabaya, 2023)
This study analyses how inclusive education is being implemented in Madrasah in Indonesia through the